The Development of an AR-Based Application for Digital Car Advertisement - AZIZAN, MUHAMMAD AKMAL; OTHMAN, MUHAMMAD FAKRI (Applied Information Technology And Computer Science, 2022)
The INFORMATIVE CARS SELLING application is a platform developed to help users find out information about Malaysian branded cars, namely Proton and Perodua, using augmented reality technology. The objective of this project is to design and develop an application using 3D methods based on the Android mobile application platform and further test the INFORMATIVE CARS SELLING application on target users who are looking for or want to buy a car. In the development of this application, the process models used is Multimedia Mobile Content Development(MMCD) which consists of five phases namely the creation of application ideas, structural analysis, design process, development of key functions and testing. The results show that it helps developers to speed up the application development process. The app uses Marker -Based Augmented Reality (Vuforia) to display 3D models and provide information on car design. The INFORMATIVE CARS SELLING application helps users to find out information regarding cars such as car models, car specifications and so on.